Changes in DPPC Liposomes Structure Induced by a 1-Carba-Alpha-Tocopherol Analogue - Neunert, Grazyna; Tomaszewska-Gras , Jolanta; Baj, Aneta; Gauza-Wlodarczyk , Marlena; Witkowski, Stanislaw; Polewski, Krzysztof (Current Topics on Chemistry and Biochemistry Vol. 2, 2022)
The interactions of the newly synthesized 1-carba-alpha-tocopherol (CT) with a 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) membrane were studied using steady-state emission spectroscopy of 1-anilino-8-naphthalene sulfonate (ANS) and 1,6-diphenyl-1,3,5-hexatriene (DPH), fluorescence anisotropy. When the concentration of CT molecules in the DPPC liposomes was raised, structural alterations were noticed, as well as the creation of distinct phases of the mixture at the same time. Temperature investigations found that decreasing temperatures resulted in a decrease in the temperature of the primary phase transition and fluidization, which was linked to increased hydration in the bilayer. The DSC results showed significant perturbations in the DPPC structure for CT concentrations as low as 2 mol%. The identification of diverse phases, such as gel, ordered liquid, disordered liquid, and liquid crystalline phases, was made possible using contour plots produced from concentration–temperature data obtained with fluorescent probes. The CT molecule inserted in the bilayer with a modified chromanol ring caused H-bonding interactions, which expelled water molecules from the interphase, creating disorder and structural modifications to the previously ordered gel phase.